NILAI TUKAR PETANI PADI SAWAH DI KECAMATAN TOMPASO BARU KABUPATEN MINAHASA SELATAN - Julietta Christi Pelengkahu; Olly Esry Harryani Laoh; Paulus Adrian Pangemanan (Sam Ratulangi University, 2019)
This study aims to determine the exchange rate of wetland rice farmers in New Tompaso District, South Minahasa Regency. This research was conducted for three months from September to November 2018. The data used were primary and secondary data. Primary data collection through direct interviews with 39 respondents of wetland rice farmers who were randomly determined. Interviews using a questionnaire prepared previously. Secondary data was collected from the Tompaso Baru District office in the form of a profile of research location, and from the internet through google searching in the form of journal articles that relevant to this research. Furthermore, the data is calculated using the formula for the exchange rate of lowland rice farmers. The results of the research that have been conducted show that the exchange rate of lowland rice farmers with an area of equal and less than 1 ha is 68.32, which means that rice farmers do not have other jobs, the farmers are unable to meet their family's daily needs. While the exchange rate of paddy rice farmers with a land area of more than 1 ha is 101.44, meaning that if the paddy farmers do not have other jobs, then the farmer is still able to meet the daily needs of his family. Thus to meet the daily needs of his family, for lowland rice farmers who only depend on the source of income from rice farming business, they must have a minimum is greater than 1 hectare of paddy field area.*eprm*